CLINICAL STUDIES ON BRL25000 (CLAVULANIC ACID-AMOXICILLIN) IN THE FIELD OF INTERNAL MEDICINE - MIURA, KENSUKE; SAWADA, HIROYOSHI; IZUMI, YOICHIRO; UCHINO, HARUTO; KINOSHITA, RYOTA; USUI, TADAO; KONISHI, HIROSHI; ISHIKURA, HIROTO; KONISHI, AKEMI (CHEMOTHERAPY, 1982)
BRL25000, one tablet of the drug containing 250 mg of AMPC and 125 mg of CVA, was administered to 13 patients with urinary or pulmonary infections. Effective results were obtained in 9 out of 10 cases with urinary infections, and one out of 3 cases with pulmonary infections. No side effects except 1 case with abdominal pain and diarrhea, were observed. This drug shows very strong antibacterial activity against several strains which are resistant to AMPC. These include E. coli, K. pneumoniae, P. mirabilis and E. cloacae. It is considered that BRL25000 may constitute an advance to the antibiotic treatment of β-lactamase proplucing bacterial infections.